Assessment of Urinary Stone Chemical Compositions and Prevalence of Metabolic Disorders Among Urolithiasis Patients in Northern Sri Lanka: A Prospective Study - Balagobi, B.; Sriskantharajah, V.; Sittampalam, R.; Vinojan, S.; Sarma, S.T.; Sunthareswaran, V.; Jothini, T.; Vishnuja, S.; Shathana, P. (Springer Nature, 2024)
Introduction Urolithiasis, a common urological disorder affecting the global population, demonstrates geographical diversity due to factors such as water quality, climate variations, health conditions, and dietary habits. This study, conducted in Northern Sri Lanka, examines urinary stone compositions and assesses the prevalence of metabolic disorders among urolithiasis patients. Methods This prospective cross-sectional study, conducted at Jaffna Teaching Hospital, Jaffna, Sri Lanka, from July 2022 to June 2023, focused on surgically treated urolithiasis patients. Institutional ethical clearance was obtained. Patient details and investigational findings were collected through questionnaires and data extraction forms. Stone analysis utilized Fourier transform infrared spectroscopy, and a detailed metabolic evaluation of a 24-hour urine collection sample was carried out. Results This study followed 153 surgically treated urolithiasis patients, primarily male (64.3%), with a mean age of 48.64. Ureteric colic (48.4%) was common, with kidney stones (45.8%) prevalent; 57.52% had recurrent stones. Diabetes mellitus (DM; 23.5%) was the top comorbidity. Calcium oxalate monohydrate (COM) stones (78.4%) were the most frequent, followed by uric acid (12.4%). COM predominated in the 40-59 age group. There was no significant gender-stone type association. A total of 86.9% had metabolic abnormalities, notably hypocitraturia (60.1%). Moreover, 23% had both hypocitraturia and hypomagnesuria. Some metabolic disorders showed gender differences, with a marginal age-metabolic disorder association (p < 0.061). Urine oxalate levels were normal, with higher variability in males. Conclusion Middle-aged males with urolithiasis commonly presented with ureteric colic and predominantly had COM stones. Recurrent stones were common, often accompanied by metabolic abnormalities such as hypocitraturia and hypomagnesuria, with DM as the primary comorbidity.
Keywords: Metabolic evaluation; Urolithiasis; Sri Lanka; Calcium oxalate; Analysis